Evangelist ali socialist - Dittrich, Marie-Agnes (Muzikološki zbornik, 2007)
At the Bach Conference 1950 in Leipzig, the socialist image of Bach in East Germany competed with the conservative and theological one of West Germany. During the Cold War both served to legitimize rival ideologies. Once again, Bach was interpreted as an orientation, as in other periods of national incertainty, like the Napoleonic Wars (Forkel, 1802) or just before the Prussian-German Empire (Wagner, 1870).
Keywords: Bach, Johann Sebastian, 1685-1750; glasba; hladna vojna; konservativna podoba Bacha; music; recepcija Bacha; socialism; socializem